P259 Interprofessional teaching on eating disorders in children: a qualitative feedback study. (June 2019) - Richardson, SC; Neylon, OM; Barrett, E
Abstract : Background: We report on an interdisciplinary training day regarding the acute assessment and management of eating disorders in paediatric settings. The Centre for Advancement of Interprofessional education defines Interprofessional education (IPE) as 'occasions when two or more professions learn with, from and about each other to improve collaboration and the quality of care'. Aim: Our aim was to assess the response to IPE teaching session on Eating disorders, a condition requiring management by a wide multidisciplinary team. Methods: An electronic survey on Survey Monkey was distributed to all registered attendees following a teaching seminar on Eating Disorders in University Hospital Limerick in November 2018. As this was an educational survey of adult learners it was deemed ethics approval was not required. Results: 41.5% (47/113) people completed the online survey. There were seven different professional groups represented. The largest group were acute setting paediatric nurses 23.4% (11/47). The majority of respondents (58.97% 23/47) work in acute paediatric services while another 30% (12/47) work in CAMHS. Over 95% (45/47) felt their learning needs were met. On a Likert scale all professional groups gave positive responses regarding their understanding of other professionals' roles in management of Eating disorders. While 44.7% (21/47) felt it changed their understanding of other professionals' role a little, a further 40.45% (19/47) felt it changed their understanding a lot. 86% (37/43) were extremely satisfied with the study day. Conclusion: The study day was well received and had a positive impact on most attendees regarding interprofessional working. In addition, other learning needs regarding eating disorders were met. Good interprofessional communication and management is the cornerstone of patient care. It is important to provide multidisciplinary education sessions which highlight the unique role each professional group brings to the management of the patient and helps to improve the understanding of the interface between different professional groups in the management of a condition.